SOCIAL INSURANCE LITERACY THROUGH ANIMATED MEDIA IN INSURANCE PERFORMANCES: LITERASI ASURANSI SOSIAL MELALUI MEDIA ANIMASI DALAM PERGELARAN ASURANSI - I Made Indra P (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
In Indonesia, there are still people who consider social insurance as something less important and feel a loss if they participate in social insurance. This is caused by the lack of literacy carried out by the government. Therefore, as a university in the field of insurance, it is necessary to carry out literacy to the community through community service. Community service in the form of social insurance literacy with performances that will be held in May-July 2022. Activities will be carried out in the form of performances by making animated videos about social insurance which include: BPJS Health, BPJS Employment and Jasa Raharja. The results of the activity evaluation showed that the level of filling out quizzes, likes and watching on the Indonesian Insurance Literacy YouTube channel, the highest for filling out the quiz was on the BPJS Health literacy material as many as 12 people, for the highest watching the YouTube channel on the Jasa Raharja material as many as 40 people while for likes had the same value as much as 3 likes